Indian diaspora in Africa : a comparative perspective - Dubey, Ajay Kumar; Organisation for Diaspora Initiatives (New Delhi, India); African Studies Association of India (New Delhi : Organisation for Diaspora Initiatives & African Studies Association of India in collaboration with MD Publications, 2010)
Contributed articles.
Includes bibliographical references.
Keywords: East Indian diaspora; East Indians -- Africa